Current Semen Extenders for Bulls - AKSU, Emrah Hicazi (Kastamonu Üniversitesi Veteriner Fakültesi, 2023)
Artificial insemination is the most widely used biotechnological application for animal breeding in cattle breeding. It is crucial to properly store the sperm obtained from the breeding bulls while maintaining their spermatological characteristic using suitable methods. During both long or short-term storage of spermatozoa, an ideal storage medium must be employed. For this purpose, diluents have been developed to meet the needs of spermatozoa. An ideal semen diluent contains ingredients that spermatozoa need, such as energy substances, protective agents against cold shock, buffering solutions that protect against pH changes, cryoprotectants to reduce damage to spermatozoa during freezing and antibiotics against microbial contamination. Semen dilution also allows for increasing the available semen volume to obtain more straws. Maintaining spermatological parameters at the best possible level during semen storage has important economic implications in this industry. For this reason, scientists continue to develop new diluents to achieve the optimum benefits from semen diluents. This review is aims to provide information about semen diluents used in bulls.
Keywords: Bull; extender; semen; storage.; Veterinary Sciences (Other); Veteriner Bilimleri (Diğer)